Marine geophysical surveys and interpretations on the ancient Eunostos harbor Area, Mediterranean Coast, Egypt - Amr Z. Hamouda; Nader H. El-Gendy; Suzan El-Gharabawy; Mahmoud Salah; Moataz Kh. Barakat (Egyptian Journal of Petroleum)
A marine geophysical survey was carried out over the ruins of the ancient Eunostos harbor, in front of the recent western harbor of Alexandria. The survey works aimed to study the seafloor and the subsurface layers over the survey area using side-scan sonar and sub-bottom profiler. It is attempted to identify the impact of nature and geo-hazards on the coast of the submerged ancient harbor. Numerous ridges, reefs and breakwaters which protected the port from the northern swells were detected on the acoustic images of the side-scan sonar. In addition to some undefined artifacts and ancient coastal scars were noticed across the seafloor. Seismic interpretations also showed series of shallow diffractions that generally intensified towards east and north. Also deformed and disturbed subsurface layers were noticed beneath the area of the submerged ancient harbor. Side-scan sonar and sub-bottom profiler findings are concordant with the descriptions of the ancient literature and succeeded to confirm the vulnerability of the ancient coastal harbor to natural disasters during the past times.